Anorexia nervosa: A pastoral update - Dayringer, Richard (Journal of religion and health, 1981)
Anorexia nervosa is a disorder of unknown etiology that is a complex of physical, emotional, and behavioral changes occurring in individuals who starve themselves. The incidence of this disease has increased dramatically in the last twenty years. Most patients seem to be unaware of or unconcerned about their emaciation. After presenting a case, this study reviews the most recent findings about this disease, including the symptoms, social characteristics of its victims, increaed incidence, history, and prognosis. Suggestions are offered for pastoral care and counseling.